AB0489 Central Neurological Manifestations in Systemic Lupus Erythematosus. (15th July 2016) - Ben Salem, T.; Tougorti, M.; Naceur, I.; Lamloum, M.; Khanfir, M.; Ben Ghorbel, I.; Houman, M.H.
Abstract : Background: Central neurological manifestations are a serious and common complication of systemic lupus erythematosus (SLE). Objectives: The aim this study was to determine the prevalence of central neurological manifestations in a group of Tunisian patients and to describe their clinical, imaging findings, their treatment and outcome Methods: A retrospective study conducted in an Internal Medicine department over a period of 14 years (from 2000 to 2013). SLE patients with central neurological manifestations (criteria of the American College of Rheumatology) were included. Clinical, laboratory data and imaging features of these patients were analyzed. Results: Fifty one patients had central neurological and /or psychiatric manifestations (20.7%). The mean age at diagnosis was 33.6±14.16 years. Sex ratio M/F was 0.10. Neurologic manifestations revealed the disease in 3.2% of SLE patients. The mean delay from SLE diagnosis to neurological manifestations was months 11.7±47.9 months. Clinically, headache was reported in 42.1% of cases and seizures in 39.4% of cases. Physical exam found: pyramidal syndrome (n=12), reflecting meningeal irritation (n=9), paraplegia (n=4) and chorea (n=2). Psychiatric manifestations were associated to neurological manifestations in 23.07% of patients: depression (n=8), anxiety disorder (n=7) and catatonia (n=2). Thirteen patients had only psychiatric manifestations: depression (n=9), anxiety disorder (n=5), catatonia (n=1). Antinuclear antibodies, anti-Sm and anti-Ribosome were positive in 49/50, 17/31 and 2/16 respectively. Aseptic meningitis was found in nine patients; lymphocytic (n=7) or polynuclear predominance (n=2). Magnetic resonance imaging (MRI) confirmed central nervous system involvement in 31 cases. Demyelinating aspect with high intensity signals were found in different localizations: periventricular (n=9), frontal (n=6), parietal (n=5), centrum semiovale (n=5), occipital (n=3). Cortical atrophy was observed in two patients. Two patients presented with stroke and one patient had cerebral venous thrombosis. MRI was normal in three patients. Antiphospholipid syndrome and Sjogren syndrome were associated to SLE in six and nine patients respectively. Patients had also arthralgia (96.1%), cutaneous manifestations (80.4%), pericarditis (31.4), pleural effusion (17.6) and lupus nephritis (37.2%). Patients were treated with antimalarial drugs (90.2%), corticosteroids (88.2%) and antiplatelet drugs (23.5%). Thirty two patients received immunosuppressive therapy: Cyclophosphamide (n=22), Azathioprine (n=9) and Methotrexate (n=1). Neurologic relapses were noted in 23, 7% of cases with a mean delay of 42.2 months. Remission was noted in 68.4% of patients with sequel in 38.4% of cases. Mean follow duration was 74.8±52.3 months. Conclusions: Prevalence of central neurological and psychiatric manifestations in systemic lupus erythematosus varies widely in different studies (20 to 97%), depending on the studies style and the including criteria. They are a real challenge for clinicians because they need to exclude other related conditions (infections, drugs, …) and primitive psychiatric disorders. Disclosure of Interest: None declared